(untitled) (International Journal of Food and Nutritional Sciences, 2019)
Zomato deals with food delivery Business. It is a Multi-National Company having Indian Origin. It aggregates different Restaurants. Zomato brought Innovative changes in culinary experience and dining options. Zomato was started in 2008 with the name of Foodie Bay by Pankaj Chaddah and Deepinder Goyal.